Layanan Unggulan sebagai Upaya Pemberian Pelayanan Berkualitas pada Pasien di RSUP Dr. Sardjito Yogyakarta - Atmim Rizki Fitriani; Elystia Vidia Marselina; Rindra Prameswari Sampadha Putri (Multidisciplinary Journal, 2022)
RSUP Dr. Sardjito Yogyakarta is a special hospital for the special regional government of Yogyakarta. RSUP Dr. Sardjito has the main task of providing public health services and implementing a referral system for the people of DIY and Southern Central Java, and is used for the benefit of the education of prospective doctors and specialist doctors by the Faculty of Medicine (FK) UGM. The main task of RSUP Dr. Sardjito Yogyakarta as a provider of health services to the community is equipped with superior services that become a benchmark for patients to seek treatment at the hospital without thinking there is any doubt about the quality that will be obtained. The purpose of this article is to find out the excellent services at RSUP Dr. Sardjito as an effort to provide quality health services for patients. The design of this study is a descriptive study that aims to describe the excellent services at Dr. RSUP. Sardjito Yogyakarta. RSUP Dr. Sardjito has several excellent services, such as integrated heart services, integrated cancer, integrated brain and vascular services, kidney transplants/grafts, IVF and eye. Some of the excellent services at RSUP Dr. Sardjito Yogyakarta is currently still based on the large volume of services served and provided to patients. RSUP Dr. Sardjito has several excellent services accompanied by complete infrastructure and health facilities as well as health workers who are competent in their fields so that they can improve the health status of Dr. RSUP Dr. Sardjito.